Out of the Margins The Rise of Chinese Vernacular Fiction - Ge, Liangyan (University of Hawaii Press, 2001)
The novel Water Margin (Shuihu zhuan), China's earliest full-length narrative in vernacular prose, first appeared in print in the sixteenth century. The tale of one hundred and eight bandit heroes evolved from a long oral tradition; in its novelized form, it played a pivotal role in the rise of Chinese vernacular fiction, which flourished during the late Ming (1368-1644) and Qing (1644-1911) periods. Liangyan Ge's multidimensional study considers the evolution of Water Margin and the rise of vernacular fiction against the background of the vernacularization of premodern Chinese literature as a whole. This gradual and arduous process, as the book convincingly shows, was driven by sustained contact and interaction between written culture and popular orality. Ge examines the stylistic and linguistic features of the novel against those of other works of early Chinese vernacular literature (stories, in particular), revealing an accretion of features typical of different historical periods and a prolonged and cumulative process of textualization. In addition to providing a meticulous philological study, his work offers a new reading of the novel that interprets some of its salient characteristics in terms of the interplay between audience, storytellers, and men of letters associated with popular orality